The effects of green perceived value and altruism on green consumption – A study on generations - Marques, Mariana Vasconcelos Taxa Tenreiro (2021)
Dissertation presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Marketing Intelligence